Two-colour interferometry and Thomson scattering measurements of a plasma gun - Hare,JD; MacDonald,J; Bland,S; Dranczewski,J; Halliday,J; Lebedev,S; Suttle,L; Tubman,E; Rozmus,W (Plasma Physics and Controlled Fusion, 2019)
We present experimental measurements of a pulsed plasma gun, using two-colour imaging laser interferometry and spatially resolved Thomson scattering. Interferometry measurements give an electron density ne ≈ 2.7 × 1017 cm−3 at the centre of the plasma plume, at 5 mm from the plasma gun nozzle. The Thomson scattered light is collected from two probing angles allowed us to simultaneously measure the collective and non-collective spectrum of the electron feature from the same spatial locations. The inferred electron densities from the location of the electron plasma waves is in agreement with interferometry. The electron temperatures inferred from the two spectra are not consistent, with Te ≈ 10 eV for non-collective scattering and Te ≈ 30 eV for collective scattering. We discuss various broadening mechanisms such as finite aperture effects, density gradients within the collective volume and collisional broadening to account for some of this discrepancy. We also note the significant red/blue asymmetry of the electron plasma waves in the collective scattering spectra, which could relate to kinetic effects distorting the distribution function of the electrons.